Anti-masking Posts on Instagram: Content Analysis During the COVID-19 Pandemic - Emma K. Quinn; Robert T. Duffy; Kristian Larsen; Maria Dalton; Cheryl E. Peters (Safety and Health at Work, 2025)
Background: The SARS-CoV-2 viral outbreak has been conflicts with the past-tense narrative elsewhere in the abstract.; the infodemic. Misinformation about the virus and disease it causes (COVID-19) has been linked with authority-questioning beliefs, co-branding with conspiracies, and other misinformation across social media. Distrust in simple occupational and public health tools we have at our disposal (like well-fitting face masks) has proliferated. Despite attempts to curb the spread of untrue or misleading information on COVID-19, this messaging persists on social media. Methods: Using a clean and cleared account, the 300 top posts under the hashtag #masksdontwork were collected on Instagram for thematic analysis over three weeks in June 2022, with three separate data collection dates. Themes contained in the posts were independently assessed by two coders and discrepancies were resolved by consensus. Results: The most dominant theme among posts was mistrust, including “government lies” and “media lies.” Anti-masking rhetoric was the second most frequent theme, where “freedom” and “disbelief in data” were common sub-themes. Conclusion: Science denial and propaganda shared among Instagram users may represent an onramp to consumption of broader conspiracy theories and government distrust, in addition to having negative health effects and social consequences for workers regardless of whether they wear masks. Social media algorithms promote similar misinformation or authority-questioning beliefs to users who view related content. Addressing the spread of health-related misinformation can assist in deconstructing myths and increasing trust in public health authorities and prevent the spread of communicable diseases among workers and the public.